The Organization of Information Technology Activities in North American Research Libraries - Mugridge, Rebecca L.; Waterhouse, Janetta (Journal of library administration, 2023)
This study presents the results of an online survey that benchmarked the organization of information technology (IT) functions in academic library members of the Association of Research Libraries. The survey investigated whether responsibility for 14 key areas resided in the libraries or in an institution-level information technology department, whether responsibilities have shifted over the past 20 years, satisfaction with services provided, assessment methods used to evaluate information technology services, and top challenges facing library IT. This paper considers the survey results addressing where the responsibility lies, satisfaction with the support, and whether and when the responsibility changed.